2016
DOI: 10.1049/iet-its.2015.0025
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability assessment approaches for intelligent transport systems: the state of the art

Abstract: The appraisal of ITS systems has become increasingly important in order to capture their full range of potential impacts. The goal of this paper is therefore to assess the appropriateness of conventional transport appraisal models and tools for this task, particularly in reflecting the environmental and socio-economic impacts of ITS. These include the most common Environmental Systems Analysis tools (ESAT), which incorporate international standards and are of considerable importance in indicating sustainabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 98 publications
0
3
0
2
Order By: Relevance
“…In recent years, a few LCA studies have been published across the spectrum evaluating the environmental impacts of the RE production process. The popular LCA database Ecoinvent (version 2.0 and subsequent versions) provides some information on the production of five REOs (lanthanum, cerium, neodymium, praseodymium, and samarium–europium-gadolinium mixture) from bastnasite at the Bayan Obo mines as a combined unit processes. , However, one should note that the actual ore composition at Bayan Obo is a mixture of bastnasite and monazite. In addition, in the Ecoinvent data set, the process emissions are based on the Mountain Pass facility.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a few LCA studies have been published across the spectrum evaluating the environmental impacts of the RE production process. The popular LCA database Ecoinvent (version 2.0 and subsequent versions) provides some information on the production of five REOs (lanthanum, cerium, neodymium, praseodymium, and samarium–europium-gadolinium mixture) from bastnasite at the Bayan Obo mines as a combined unit processes. , However, one should note that the actual ore composition at Bayan Obo is a mixture of bastnasite and monazite. In addition, in the Ecoinvent data set, the process emissions are based on the Mountain Pass facility.…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth analysis of specialist literature [23][24][25] indicated that despite some publications on the improvement in efficiency observed at various organisations, the significance and role of IT systems in increasing organisational efficiency have been relatively scarcely discussed [26]. Most frequently, such considerations have been side-effects resulting from major discussions on other problems [3,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors (De Gruyter, Currie & Rose, 2016;Kolosz & Grant-Muller, 2016) have focused their sustainability studies on transport processes owing to its impact on today's world. According to the United Nations Conference on Trade and Development (UNCTAD), sustainable freight transport systems entail, among other features, "the ability to provide transportation that is safe, socially inclusive, accessible, reliable, affordable, fuel-efficient, environmentally friendly, low-carbon, and resilient to shocks and disruptions, including those caused by climate change and natural disasters" (UNCTAD, 2015).…”
Section: Introductionmentioning
confidence: 99%